Plantar pressure distribution profile of type 2 diabetes mellitus with diabetic foot syndrome: A hospital-based observational study - H. Ya. Korada; E. Arora; Sh. K. Rao; M. Hande; S. Shetty; A. G. Maiya (Сахарный диабет)
INTRODUCTION: The prevalence of diabetic foot syndrome is increasing in the Indian population. It is a triad of neurological, vascular, and biomechanical changes due to long term diabetes mellitus (DM). Altered plantar pressure distribution is a risk factor for developing diabetic foot ulcers. The purpose of this study is to evaluate the altered plantar pressure distribution in diabetic peripheral neuropathy individuals with peripheral vascular disease in comparison with diabetic peripheral neuropathy and non-diabetic neuropathy. Therefore, the objective of the study is to evaluate the plantar pressure distribution and parameters in type 2 DM (T2DM) with diabetic foot syndrome.METHODS: In this study, 60 participants with T2DM were recruited in either one of the three groups: 20 Diabetic non-neuropathy (DNN), 20 Diabetic peripheral neuropathy (DPN), and 20 Diabetic peripheral neuropathy with the peripheral arterial disease (DNPAD). Then we compared the plantar pressure parameters like maximum plantar pressure, pressure-time integral, fore foot-hind foot ratio, and total contact area were measured using a WinTrack plantar pressure system.RESULTS: The diabetic peripheral neuropathy with peripheral vascular disease group shown a significant difference in all the  plantar pressure parameters measured in comparison with the diabetic peripheral neuropathy group. There was increased Maximum plantar pressure, pressure-time integral and forefoot hindfoot ratio, and reduced total contact area of the foot (p < 0.05).CONCLUSION: For patients, with combined peripheral neuropathy and peripheral vascular disease have increased plantar pressure distribution, are at higher risks of developing neuro-ischemic foot, which further leads to diabetic foot ulcers.